BoerPE Goat Blood Profile as Indicators of Crossbreeding Resistance - Dedi Suryanto; Inggit Kentjonowaty; Nurul Humaidah (UNIVERSITAS ISLAM LAMONGAN, 2020)
Cases of clinical reproduction in crossbred cattle have been reported with the incidence of decreased reproductive performance. Crossbreeding resistance is usually followed by low immunity. Blood profile is one of the parameters that illustrate the immunity of livestocks. Goat crossbreeding resistance has never been studied. The purpose of this study was to analyze the crossbreeding resistance of the F1 BoerPE goat and her mothers by analyzing their blood profile. F1 BoerPE goat is the offspring of crossbreeding between Boer buck with PE goat. The research method was case study. The primary data were obtained from examination of blood profile and Physiological Status of F1 BoerPE goat and her mothers. The secondary data obtained from recording age and body weight. The blood profile data were analyzed by t test. The observed blood profile indicators were neutrophils, monocytes and lymphocytes. The results showed that the physiological status of F1 BoerPE goat and her mothers was not significant. Nevertheless, the number of neutrophils, lymphocytes and monocytes was significantly different (p˂0.01). The average (%) number of neutrophils, lymphocytes and monocytes of PE goats was 37.92 ± 1.37; 51.85 ± 1.4; 3.87 ± 0.21. while the average blood profile of F1 BoerPE was 46.16 ± 2.1; 58.06 ± 3.4; 5.51 ± 0.18. The average number of neutrophils, lymphocytes and monocytes F1 BoerPE goat was higher compared to the parent. It is indicated that there were crossbreeding resistance of F1 BoerPE goat.